MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN PROSES MANAJEMEN PENGETAHUAN - Maula, Rina Rahma; Sasana, Hadi (Transpublika Publisher, 2022)
Human Resources or commonly referred to as HR are individuals who are productive and contribute to an organization or company, where these individuals are important assets for a company. While the meaning of management is a process of planning and monitoring that exists in an organization to achieve the goals that have been set within the organization. In this study the author will discuss about Human Resource Management which is a plan in the supervision of HR in a company or other organization. This research aims to find out how the strategy of human resource management system can improve the quality of human resource management itself. This study explores Human Resource Management (HR) in increasing their knowledge of company or organization management. This study explores how the system used to collect and store data needed by an organization about HR activities and characteristics in improving knowledge management operations. The data was collected through a survey with a literature review. The results showed that HRM practice is an initiative in the process of improving the knowledge management strategy applied to the organization. Each HRM subcomponent influences the knowledge management component and we can conclude that HRM is highly influential and has a positive impact on the quality control process and vice versa in the work environment.